Blood eosinophil count to predict bronchial eosinophilic inflammation in COPD. Issue 5 (4th February 2016) - Schleich, Florence; Corhay, Jean-Louis; Louis, Renaud
Chronic obstructive pulmonary disease (COPD) is an inflammatory disease of the airways. There is evidence that maintenance treatment with inhaled corticosteroids (ICS) in COPD results in a reduction in the mean rate of exacerbations, and improvement in quality of life and lung function [1]. However, ICS therapy has been associated with increased risk of oropharyngeal candidiasis, hoarseness and pneumonia [1]. In COPD, ICS are now recommended in cases of frequent exacerbations and severe obstruction [2]. Blood eosinophil counts, but not F eNO, may predict airway eosinophilic inflammation http://ow.ly/WXgkA